The East Asian pop fandom an analysis of the motivations and gains of the Filipino audience in consuming Japanese and Korean popular culture - Atienza, Noriza Sunga; Encanto, Georgina (2012)
"The rise of the popularity of East Asian pop is not only a phenomenon observable in the Philippines, but rather a part of the growing global attention on the entertainment industry of Japan and Korea. Employing the Uses and Gratification Theory, this study analyzes the motivations of fans of Japanese and Korean pop culture in consuming the media products and what they actually gain from doing so. Furthermore, various cultural factors that are found to be determinant of the fans' preference for particular popular media content and genre were also analyzed, most notable the notion of Cultural Proximity propositioned by Staubhaar. These Japanese and Korean pop fans are active in choosing which cultural products they consume. Although J-pop and K-pop require relatively more effort to access compared to the local counterparts, the fans go to great lengths because they opt to know more about, watch and listen to something different and unlike the culture they have been exposed to. The study also determines the cognitive, affective and behavioral effects of consuming the media contents, achored on the Media Dependency Theory developed by Ball-Rokeach and DeFleur."
Vita.
Undergraduate thesis (A.B. Journalism)--University of the Philippines.
Keywords: Popular culture -- Japan; Popular culture -- Korea